2021
DOI: 10.1177/0734371x211030320
|View full text |Cite
|
Sign up to set email alerts
|

Human Resources in Multilevel Service Provision Performance: The Role of Field Offices and Local Organizations

Abstract: The public management literature has extensively explored human resources’ (HR) contribution to organizational performance. However, HR approaches are seldom explored when assessing multilevel service provision. This research studies the HR-performance relationship when organizations at different government levels contribute to service provision. Beyond directly engaged local organizations, HR in national organizations’ field offices providing ancillary services may influence local service performance; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Therefore, the types of knowledge and access to networks provided by specific public offices seem to affect performance. Future research should explore whether transferring of top‐down experience matters for performance across other policy areas, such as securing grants (e.g., Avellaneda, 2012), social service provision (e.g., Bello‐Gomez, 2023), tax collection (e.g., Petrovsky & Avellaneda, 2014), personnel recruitment, and participatory decision‐making. Moreover, this study finds a significant relationship between some of the characteristics considered by mayors when appointing their chief planning officers (key players for the planning process and for the administration overall) and the midterm achievement of strategic goals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the types of knowledge and access to networks provided by specific public offices seem to affect performance. Future research should explore whether transferring of top‐down experience matters for performance across other policy areas, such as securing grants (e.g., Avellaneda, 2012), social service provision (e.g., Bello‐Gomez, 2023), tax collection (e.g., Petrovsky & Avellaneda, 2014), personnel recruitment, and participatory decision‐making. Moreover, this study finds a significant relationship between some of the characteristics considered by mayors when appointing their chief planning officers (key players for the planning process and for the administration overall) and the midterm achievement of strategic goals.…”
Section: Discussionmentioning
confidence: 99%
“…The finding on hierarchy suggests an inward orientation on the part of health system actors that warrants additional investigation. This is because there is an ongoing debate about what types of influence more central actors continue to exercise within decentralized contexts (Bello‐Gomez, 2023; Schillemans, 2008), and recent research has identified the important role that cross‐level ties play in facilitating cooperation in local service delivery (Molina‐Garzón et al, 2022). Additional research on this point could also benefit from using a more nuanced measure of hierarchy that maps closely onto the levels within the existing service delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…Creating human resources through official education is also one way of improving the quality of human resources resulting from the Vocational Education program, which aims to create human resources in government that meets service needs at the local level (Bello-Gomez, 2023). Every student at an educational institution must fulfill the following and adapt to developments in technology and information, as well as changing Brazilian Journal of Development, Curitiba, v.10, n.1, p. 1623Curitiba, v.10, n.1, p. -1636Curitiba, v.10, n.1, p. , jan., 2024 working methods (Akour & Alenezi, 2022).…”
Section: Introductionmentioning
confidence: 99%